The lost history of Christianity : the thousand-year golden age of the church in the Middle East, Africa, and Asia- and how it died - Jenkins, Philip, 1952- (New York : HarperOne, 2008)
A lost history revealing that, for centuries, Christianity's center was actually in the Middle East, Asia, and Africa, with significant communities extending as far as China.
A note on names and -isms -- The end of global Christianity -- Churches of the East -- Another world -- The great tribulation -- The last Christians -- Ghosts of a faith -- How faiths die -- The mystery of survival -- Endings and beginnings.
Includes bibliographical references (p. [263]-297) and index.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Christian civilization; Civilization, Arab -- Christian influences; Middle East -- Church history; Africa, North -- Church history; Asia -- Church history